In situ detection of alkaline phosphatase in a cisplatin-induced acute kidney injury model with a fluorescent/photoacoustic bimodal molecular probe - Chen, Xingwang; Yuwen, Zhiyang; Zhao, Yixing; Li, Haixia; Chen, Kang; Liu, Hongwen (Frontiers in Bioengineering and Biotechnology, 2022)
Kidneys play an important part in drug metabolism and excretion. High local concentration of drugs or drug allergies often cause acute kidney injury (AKI). Identification of effective biomarkers of initial stage AKI and constructing activable molecular probes with excellent detection properties for early evaluation of AKI are necessary, yet remain significant challenges. Alkaline phosphatase (ALP), a key hydrolyzing protease, exists in the epithelial cells of the kidney and is discharged into the urine following kidney injury. However, no studies have revealed its level in drug-induced AKI. Existing ALP fluorescent molecular probes are not suitable for testing and imaging of ALP in the AKI model. Drug-induced AKI is accompanied by oxidative stress, and many studies have indicated that a large increase in reactive oxygen species (ROS) occur in the AKI model. Thus, the probe used for imaging of AKI must be chemically stable in the presence of ROS. However, most existing near-infrared fluorescent (NIRF) ALP probes are not stable in the presence of ROS in the AKI model. Hence, we built a chemically stable molecular sensor (CS-ALP) to map ALP level in cisplatin-induced AKI. This novel probe is not destroyed by ROS generated in the AKI model, thus allowing high-fidelity imaging. In the presence of ALP, the CS-ALP probe generates a new absorbance peak at 685 nm and a fluorescent emission peak at 716 nm that could be used to “turn on” photoacoustic (PA) and NIRF imaging of ALP in AKI. Levels of CS-ALP build up rapidly in the kidney, and CS-ALP has been successfully applied in NIRF/PA bimodal in vivo imaging. Through the NIRF/PA bimodal imaging results, we demonstrate that upregulated expression of ALP occurs in the early stages of AKI and continues with injury progression.